A cute little murder - Harper, Molly (Berkley Mystery, 2026)
"She used to be the sidekick. Now she might be the only one who can survive. As teens, Harlow Drake and Lainey Piper built an online fandom solving small-town crimes. Harlow was the star, Lainey the behind-the-scenes genius (and often, Harlow's scapegoat). Years later, Harlow's hosting a hit true crime tv show. Lainey? She's working in forensic. Well, forensic accounting ... from home. In pajamas. With her cat. But when Harlow faces significant backlash over fumbling a case, she needs a quick win-like a special investigation into the decades-old disappearance of a starlet from a once-glamorous, now decrepit island hotel. The catch? It's bankrolled by Deke and Bryce of DBag Games, who are looking to shed their "frat bro" reputations. As long-time fans, they have one requirement for their funding: Lainey has to play the sidekick again. Lainey is wary, but the offer is a lifeline in sea of unpaid student loans. After reaching the Crossings Hotel, she realizes she's not content to be Harlow's helper anymore. As the cold case heats up, a crew member falls over dead, presenting Harlow and Lainey with a more current mystery: Are they really alone on the island? It's clear the hotel hides more secrets in its walls. With sabotage, hidden staircases, and a killer in their midst, Lainey steps into the spotlight and takes charge of the investigation. It's up to her to crack the case-as long as she can stay alive"-- Provided by publisher.